Management of endometriosis-related infertility: Considerations and treatment options - Lee, Dayong; Kim, Seul Ki; Lee, Jung Ryeol; Jee, Byung Chul (Clinical and experimental reproductive medicine, 2020)
Endometriosis is a common inflammatory disease in women of reproductive age and is one of the major causes of infertility. Endometriosis causes a sustained reduction of ovarian reserve through both physical mechanisms and inflammatory reactions, which result in the production of reactive oxygen species and tissue fibrosis. The severity of endometriosis is related to ovarian reserve. With regard to infertility treatment, medical therapy as a neoadjuvant or adjuvant to surgical therapy has no definite beneficial effect. Surgical treatment of endometriosis can lead to ovarian injury during the resection of endometriotic tissue, which leads to the deterioration of ovarian reserve. To overcome this disadvantage, a multistep technique has been proposed to minimize the reduction of ovarian reserve. When considering surgical treatment of endometriosis in patients experiencing infertility, it should be kept in mind that ovarian reserve can be reduced both due to endometriosis itself and by the process of removing endometriosis. In cases of mild- to moderate-stage endometriosis, intrauterine insemination with ovarian stimulation after surgical treatment may increase the likelihood of pregnancy. In cases of severe endometriosis, the characteristics of the patient should be considered in a multidisciplinary manner to determine the prioritization of treatment modalities, including surgical treatment and assisted reproduction methods such as in vitro fertilization. The risk of cancer, complications after pregnancy, and infection during oocyte retrieval should also be considered when making treatment decisions.